Suplementação de cromo na dieta, utilização de carboidrato e desempenho produtivo do pacu (Piaractus mesopotamicus) - Baldan, Ana Paula [UNESP] (2004)
The efficiency of the utilization of dietary protein by fish can be improved by increasing other dietary energy sources, e.g. lipid and carbohydrate, in the diet. Studies have shown that there is an effect of the chromium in carbohydrate metabolism, but other investigations have assumed that the chromic oxide, widely used as marker in digestibility assays, is inert, not absorbed and does not affect the digestive physiology of fish. This study evaluated the energetic metabolism and growth performance of pacu (Piaractus mesopotamicus), a frugivorous species, fed diets supplemented with chromic oxide. Two hundred eighty-eight juveniles of four weight classes (21.2±1.87; 27.8±1.76; 34.1±1.63; 41.4±1.83g), distributed in 24 polyethylene boxes (100L, 12 per box), were fed) (0, 10, 50, 100, 300 e 1000 mg kg-1). Fish were sampled with an isonitrogenous and isoenergetic diet supplemented with six levels of chromic oxide (Cr2O3after 30 and 60 days of feeding. The metabolic parameters analyzed were: plasma glucose, serum total protein, triacylglycerids and cholesterol, muscle lipid, liver lipid and glycogen, hepatosomatic and fat visceral indexes. The growth parameters evaluated were: weight gain, feed conversion ratio, protein efficiency ratio, specific growth rate, relative feed intake, and chromic oxide feed intake. The metabolic parameters and growth performance of pacu were not altered by effect of chromic oxide supplementation (P>0,05). A t the 30 last days of feeding, fish had better growth performance. These results suggest that the chromium, in form of oxide, had no significant effect on the utilization of dietary carbohydrate by pacu